Retrieval Rapid Emergency Medical Score in retrieval medicine. (20th September 2015) - Kennedy, Marcus P; Wilson, Krystle; Gabbe, Belinda J; Straney, Lahn; Bailey, Michael
Abstract: Objective: Prognostic models are commonly used in the clinical setting. The objective of the study is to evaluate the prognostic accuracy of the Rapid Emergency Medical Score (REMS) or alternate models. Methods: A retrospective cohort study of critical care patients who underwent retrieval service transfer to an ICU in a single state‐wide service in Victoria, Australia. All patients aged 18 years and over transferred to an ICU between 1 January 2010 and 30 June 2013. Retrieval and ICU datasets were probabilistically linked. Multivariable logistic regression modelling was used to investigate the capacity of physiological markers and patient characteristics to predict in‐hospital mortality in the ICU population. The prediction performance was evaluated using measures of discrimination (C‐statistic) and calibration (Hosmer–Lemeshow [H‐L statistic] ). Results: There were 1776 ICU patients who were transferred and 1749 (98.5%) had complete data. Of the 1749 patients with complete data, 257 (14.7%) died in‐hospital. The REMS calculated at the time of retrieval referral demonstrated borderline predictive capability (C‐statistic 0.69, 95% CI 0.62–0.76). Following logistic regression analysis of the REMS components, final variables included in the Retrieval REMS model were age, mean arterial pressure and Glasgow Coma Scale score. This model demonstrated acceptable predictive capability (C‐statistic 0.72, 95% CI 0.64–0.79). The median (interquartile range [IQR]) Retrieval REMS for survivors and non‐survivors, respectively, were 7 (5, 10) and 9 (7, 11), P < 0.01. Conclusions: The availability of a validated tool such as Retrieval REMS assists recognition of high‐risk patients and consideration of this risk in retrieval mission planning and response.